A calibration of the triple oxygen isotope fractionation in the SiO2–H2O system and applications to natural samples. (1st August 2016) - Sharp, Z.D.; Gibbons, J.A.; Maltsev, O.; Atudorei, V.; Pack, A.; Sengupta, S.; Shock, E.L.; Knauth, L.P.
Abstract: It is now recognized that variations in the Δ 17 O of terrestrial materials resulting from purely mass dependent fractionations, though small, have geological significance. In this study, the δ 18 O and δ 17 O values of selected low temperature quartz and silica samples were measured in order to derive the quartz-water fractionation–temperature relationship for the three oxygen isotope system. A 18 O/ 16 O quartz-water fractionation equation valid for all temperatures was generated from published high temperature exchange experiments and low temperature empirical estimates and is given by 1000 ln α qz- H 2 O 18 O / 16 O = 4.20 ( 0.11 ) × 10 6 T 2 - 3.3 ( 0.2 ) × 1000 T ( T in Kelvins). The equilibrium δ 17 O– δ 18 O relationship is given by the equation ln α 17 O / 16 O = θ ln α 18 O / 16 O . The variation of θ with temperature for the quartz-water system was determined empirically using low temperature marine diatoms, microcrystalline quartz and a modern sinter sample. A best fit to the data give the equation θ SiO 2 – H 2 O = - ( 1.85 ± 0.04 ) T + 0.5305, indistinguishable from an earlier theoretical estimate. Application of the quartz-water triple isotope system to low temperature samples provides constraints on both temperature and composition of the water with which the silica last equilibrated. Authigenic quartz crystallization temperatures cluster around 50 °C, which are lower than many previous estimates. The combined δ 18 O and δ 17 O values of samples considered to be in equilibrium with ocean or meteoric waters can be used to estimate both formation temperatures and the δ 18 O value of the meteoric water. Unlike other multiple isotopes systems, such as combined H and O isotopes in cherts, the oxygen source and diagenetic potential for both 17 O/ 16 O and 18 O/ 16 O ratios are identical, simplifying interpretations from ancient samples.